Genealogy of Religious Study Program of Uin Ar-Raniry Aceh in Developing the Values of Religious Moderation - Mawardi (Jayapangus Press, 2022)
This study aimed to describe the genealogy of the Religious Studies Program of UIN Ar-Raniry Aceh in developing the value of religious moderation. Religious moderation is an attitude, perspective, mindset, and way of behaving in carrying out religion with the nature of tawassuth (middle), tawazun (balanced), and tolerance. In principle, the purpose of religious moderation is harmony. In Indonesia, the development of religious studies in other higher education institutions is encouraging news so that the search for religious conventions can provide more alternatives. This study was conducted using a qualitative method that produces descriptive data with a phenomenological approach. Data collection techniques used were observation, interviews, and documentation with inductive data analysis. The results showed that the Indonesian government’s efforts to ground the values of religious moderation through the mouthpiece of the Ministry of Religious Affairs have strategic values, but it is not as easy as turning the palm, it will solve the intolerance problem.